2014
DOI: 10.1002/14651858.cd011406
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy followed by autologous haematopoietic cell transplantation for children, adolescents and young adults with first recurrence of Ewing sarcoma

Abstract: High-dose chemotherapy followed by autologous haematopoietic cell transplantation for children, adolescents, and young adults with first recurrence of Ewing sarcoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In those patients who present with pulmonary metastases, the 2- to 10-year event-free survival lies around 30–36% within the European Intergroup Cooperative Ewing and Paediatric Oncology Group studies [ 17 ]. Multivariable analysis of the European EURO-E.W.I.N.G.-99 trial (EUROpean Ewing tumour Working Initiative of National Groups-Ewing Tumour Studies 1999), on patients with primary disseminated multifocal Ewing sarcoma, identified several factors that significantly correlate with a worse outcome: patient age of more than 14 years at diagnosis, initial tumor volume of ≥200 mL, bone marrow metastases, and additional lung metastases [ 18 , 55 ]. Adverse clinical prognostic factors for patients with non-metastatic Ewing sarcoma are the site of the primary tumor (with axially located tumors with a poorer prognosis), poor histological response after neoadjuvant (radio-)chemotherapy (10% or greater viable tumor cells), and elevated serum lactate dehydrogenase levels [ 55 , 56 , 57 ].…”
Section: Ewing Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…In those patients who present with pulmonary metastases, the 2- to 10-year event-free survival lies around 30–36% within the European Intergroup Cooperative Ewing and Paediatric Oncology Group studies [ 17 ]. Multivariable analysis of the European EURO-E.W.I.N.G.-99 trial (EUROpean Ewing tumour Working Initiative of National Groups-Ewing Tumour Studies 1999), on patients with primary disseminated multifocal Ewing sarcoma, identified several factors that significantly correlate with a worse outcome: patient age of more than 14 years at diagnosis, initial tumor volume of ≥200 mL, bone marrow metastases, and additional lung metastases [ 18 , 55 ]. Adverse clinical prognostic factors for patients with non-metastatic Ewing sarcoma are the site of the primary tumor (with axially located tumors with a poorer prognosis), poor histological response after neoadjuvant (radio-)chemotherapy (10% or greater viable tumor cells), and elevated serum lactate dehydrogenase levels [ 55 , 56 , 57 ].…”
Section: Ewing Sarcomamentioning
confidence: 99%
“…Adverse clinical prognostic factors for patients with non-metastatic Ewing sarcoma are the site of the primary tumor (with axially located tumors with a poorer prognosis), poor histological response after neoadjuvant (radio-)chemotherapy (10% or greater viable tumor cells), and elevated serum lactate dehydrogenase levels [ 55 , 56 , 57 ]. Besides patient characteristics, the success of the local tumor therapy affects the global outcome [ 55 , 58 ]. About 26% of primary tumors are located in the pelvis [ 57 , 59 ].…”
Section: Ewing Sarcomamentioning
confidence: 99%